Oxygen filling voids and direct element imaging of metastable ZnSb structures by aberration-corrected scanning transmission electron microscopy. (December 2018) - Wang, Guoxiang; Lotnyk, Andriy; Li, Chao; Shen, Xiang
Abstract: Void formation in metastable ZnSb structures has yet to be investigated. We developed a technique to fill voids caused by Sb diffusion, through the introduction of oxygen dopants into the metastable ZnSb phase. This filling of voids enables their role in phase-change processes to be accurately investigated. Our scanning transmission electron microscopy investigations showed that oxygen dopants repaired voids through recovery of bond connectivity. This approach stabilizes a metastable phase and avoids the metastable-to-stable phase transformation. Our characterization of void defects sheds light on the long-standing puzzle of the metastable-to-stable phase transition mechanism. Graphical abstract: Unlabelled Image